Assessing the relevance, applicability and conditions of a spatial information system for local development planning and management a case study of the municipality of Baler, Aurora province, the Philippines - Rahman, MD. Taibur (2006)
Development authorities are increasingly being required to operate faster, more efficiently, and with lower budgets, while facing fast growth and an ever increasing number of political and regulatory issues. The collection, management, analysis and dissemination of information have become some of the most important functions that an LGU must perform. In the Philippine context, development plans have to be developed and mandated by the LGC ever since 1991, to guide and promote sustainable development. Along with the other management functions of the LGU, managing property ownership and taxation records has become critical to the survival of some local governments. Efficient disaster management is also another crucial issue. To improve all these processes, efficient and integrated information systems are required. New IT, GIS, RS, Web and engineering technology have become available to offer Local Government Units (LGU) these information systems that help to manage the above-mentioned planning and management tasks more efficiently and effectively. By integrating geographic information systems, analysis and decision-making will be improved, leading to better services for the public. The Local Government Code of 1991 does not only provide the opportunity for Local Government Units to formulate their own development plan. These two plans, however, are not that easy to prepare particularly for a remote local government such as that of Baler where are neither human resources nor infrastructure and technology. Their main constraint to preparing the CDP and CLUP are data unavailability, especially geo-referenced data. This means that the maps are not really updated and are not digitized in most cases. The maps found in the developed CDP and CLUP are illegible and obsolete. As a result, th equality of the CLUP document, in terms of spatial information presentation and spatial decision-making, is not really good for the LGU under study. Furthermore, the LGU also prepares some plan, natural resource management plan, and others.. Three-fourths of the effort is devoted to data collection to prepare any of these documents. The absence of a digital database results in duplication of efforts and leads to data inconsistency in the various plan documents. An information system is suitably fit for local government functions. Voluminous data on land use are collected, created, and used. An information system could help organize, store, and process these data for easy access,analysis, and dissemination among the municipal officials of different departments and other development stakeholders. Furthermore, land use deals with space and time. A considerable part of the activities and decisions of local government involve spatial information. One estimate shows that more than 80% of the data needed by government, businesses, and private individuals have to do with the location of people, places, things, and events (NAMRIA, 2000). Thus, an information system that can handle spatial and non-spatial data could be a valuable resource for local government....